Final report on the 1986 census of agriculture in Saint Lucia (Ministry of Agriculture, Lands, Fisheries and Cooperatives CastriesLC, 1987)
Tables provide data on number and size of holdings by forms of tenure, area in holdings, land distribution by sex of holder, land utilization, age and occupation of holder, size of farm households, number of farm workers, size of farm income, number of holdings growing specified crops and/or livestock, distribution of crops and livestock, use of fertilizers and selected farm inputs. Presents a comparative analysis of the 1973/74 and the 1986 censuses.
Chiefly statistical data